Modernizing Cash Management - Lienert, Ian (Technical Notes and Manuals; Technical Notes and Manuals ;, 2009)
This technical note describes the objectives of modern cash management. The note highlights that cash management is necessary because there are mismatches between the timing of payments and the availability of cash. All definitions of cash management emphasize the time value of government money. This note elaborates good cash management practices in developed countries, and the main features of the framework for short-term cash planning. Challenges for improving cash management in low- and middle-income countries are also discussed.